Used Oil Refining Process by Using Green Tea Waste for Floor Cleaner With An Addition of Pineapple Skin Extract - Yustinah, Yustinah; Wulandari, Qodriani Apri; Nabilah, Rifa; Arifka, Angelia Ainun (Universitas Negeri Semarang, 2024)
Used cooking oil is a waste that is produced every day and is increasing. Used cooking oil cannot be consumed again because it contains dangerous substances that will cause disease, but it also cannot be thrown away since it will pollute the environment. Therefore, it is necessary to process used cooking oil, one of which is purification using the adsorption method. The adsorption method for used cooking oil can be derived from green dregs because greens contain antioxidants which can reduce the content of dangerous substances in used cooking oil. In this study, we used variations in adsorbent mass (10 gr, 20 gr, 30 gr, 40 gr, and 50 gr) and stirring time (25 minutes, 45 minutes, 65 minutes, 86 minutes, and 105 minutes) to obtain the highest purification results. was the best and it was found that the adsorbent mass of 50 grams of green dregs and a stirring time of 105 minutes had the best results in being able to reduce the peroxide value, air content and free fatty acids. Next, the purified used cooking oil will be processed into floor cleaning liquid soap with the addition of 2 ml, 4 ml, 6 ml, 8 ml and 10 ml of pineapple peel extract. The results of the floor cleaning soap showed that the best results were 2 ml based on the alkaline number, pH and anti-bacterial test.